The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.21273/jashs.119.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Cold Acclimation and Alterations in Protein Synthesis in Bermudagrass Crowns

Abstract: Cold acclimation (CA) of `Midiron' and `Tifgreen' turf bermudagrasses (Cynodon dactylon L. Pers. × C. transvaalensis Burtt-Davy) induced tolerance to lower freezing temperatures and altered protein synthesis in crowns. LT50 (lethal temperature for 50% of plants) values were lowered ≈5C after 4 weeks in controlled-environment chambers under CA [8/2C (day/night) cycles with a 10-hour photoperiod] vs. non-CA (28/24C) conditions. LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Bermudagrass is the most widely used warm‐season turfgrass species on golf courses in the southern US due to aggressive growth and high recuperative capacity following traffic/wear (6,24,30). Recent improvements in the cold tolerance of several new bermudagrass cultivars have extended its use further north (3,23). Although less tolerant of cold temperatures than zoysiagrass and buffalograss, bermudagrass may be successfully cultivated in the southern and central regions of the transition zone (3,30).…”
Section: Spring Dead Spot Diseasementioning
confidence: 99%
“…Bermudagrass is the most widely used warm‐season turfgrass species on golf courses in the southern US due to aggressive growth and high recuperative capacity following traffic/wear (6,24,30). Recent improvements in the cold tolerance of several new bermudagrass cultivars have extended its use further north (3,23). Although less tolerant of cold temperatures than zoysiagrass and buffalograss, bermudagrass may be successfully cultivated in the southern and central regions of the transition zone (3,30).…”
Section: Spring Dead Spot Diseasementioning
confidence: 99%
“…Bermudagrass, Cynodon dactylon (L.) Pers., is an important perennial grass species in the botanical family Poaceae [26]. Originally native to Africa, C. dactylon has become naturalized in many places around the world and is widely distributed in tropical, subtropical, and temperate coastal areas [27].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous research identified several physiological and metabolic changes by cold stress in bermudagrass, including protein synthesis, chitinase and dehydrin expression, amino acid metabolism, etc. (Gatschet et al 1994(Gatschet et al , 1996Anderson et al 2002;Zhang et al 2006Zhang et al , 2011aZhang et al , 2011bMunshaw et al 2011), the early signal transduction of cold stress responses in bermudagrass are largely unknown.…”
Section: Introductionmentioning
confidence: 99%